2009
DOI: 10.1507/endocrj.k09e-089
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Regulates Hippocampal Neurogenesis in Adult Mice

Abstract: Rapid CommuniCationis principally released from Gr cells in the oxyntic mucosa of the stomach [5]. In addition to stimulating GH release via the hypothalamus and direct pituitary pathways and inducing a positive energy balance by stimulating food intake while decreasing fat use through GH-independent mechanisms, ghrelin has been suggested to have numerous peripheral actions including direct effects on exocrine and endocrine pancreatic functions, carbohydrate metabolism, the cardiovascular system, gastric secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 23 publications
2
98
0
2
Order By: Relevance
“…Initially, ghrelin was known to increase neurogenesis in the rat fetal spinal cord (Sato et al 2006) and the nucleus of the solitary tract (Zhang et al 2005) and the dorsal motor nucleus of vagus in adult rats. We previously reported that systemic administration of ghrelin induces hippocampal neurogenesis in adult mice (Moon et al 2009b). Moreover, in our recent study (Li et al 2013), we found that ghrelin knockout mice showed lower numbers of progenitor cells in the DG of the hippocampus, while ghrelin treatment restored the numbers of progenitor cells to those of the wild-type controls.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Initially, ghrelin was known to increase neurogenesis in the rat fetal spinal cord (Sato et al 2006) and the nucleus of the solitary tract (Zhang et al 2005) and the dorsal motor nucleus of vagus in adult rats. We previously reported that systemic administration of ghrelin induces hippocampal neurogenesis in adult mice (Moon et al 2009b). Moreover, in our recent study (Li et al 2013), we found that ghrelin knockout mice showed lower numbers of progenitor cells in the DG of the hippocampus, while ghrelin treatment restored the numbers of progenitor cells to those of the wild-type controls.…”
Section: Introductionmentioning
confidence: 65%
“…In the current study, we clearly showed that the ghrelin receptor was expressed in cultured adult rat hippocampal NSCs at the protein levels, which were assessed by two independent methods (western blot analysis and immunocytochemistry). GHS-R1a was also found in hippocampal progenitor cells in adult mice (Moon et al 2009b). The effect of ghrelin on the proliferation of adult rat hippocampal NSCs appears to be mediated through the activation of GHS-R1a because the treatment of the receptor-specific antagonist D-Lys-3-GHRP-6 completely blocked the proliferative effect of ghrelin.…”
Section: Discussionmentioning
confidence: 90%
“…Levels of brain-derived neurotrophic factor protein in the hippocampus were similar between WT and GKO mice, and were increased by DR both in WT and GKO mice. These results suggest that elevated levels of ghrelin during DR may have an important role in the enhancement of neurogenesis induced by DR.Key words: Ghrelin, Adult neurogenesis, Hippocampus, Dietary restriction lar zone (SGZ) [6]. Additionally, in our recent report [7], we found that mice with targeted disruption of the ghrelin gene showed a decreased number of progenitor cells in the dentate gyrus (DG) of the hippocampus, while ghrelin replacement restored progenitor cell numbers to those of wild-type (WT) controls.…”
mentioning
confidence: 94%
“…Key words: Ghrelin, Adult neurogenesis, Hippocampus, Dietary restriction lar zone (SGZ) [6]. Additionally, in our recent report [7], we found that mice with targeted disruption of the ghrelin gene showed a decreased number of progenitor cells in the dentate gyrus (DG) of the hippocampus, while ghrelin replacement restored progenitor cell numbers to those of wild-type (WT) controls.…”
mentioning
confidence: 96%
“…Initially, ghrelin was shown to increase neurogenesis in the dorsal motor nucleus of vagus [4], the nucleus of the solitary tract [5] and the rat fetal spinal cord [6] in adult rats. We recently have reported that systemic administration of ghrelin stimulates proliferation of newly generating cells in the hippocampus of adult mice [7]. Moreover, immunoneutralization of ghrelin by using anti-ghrelin antiserum in adult mice reduces proliferation of hippocampal progenitor cells in the SGZ [7].…”
mentioning
confidence: 99%